Transient Analysis of Force Convective Solar Air Heater - Ahmad Zaini, Nur Hamizah (2018)
This project was aimed to study the thermal transfer and effectiveness of graphene as absorber plate in a multi-pass solar air heater with forced convection by solving a partial differential equation through implicit technique with the usage of Partial Differential Equation Toolbox of MATLAB software. The heat transfer relationship between all parts of the multi-pass solar air heater were considered for an energy balance equation. Transient analysis are conducted using recorded solar irradiance for 36000 seconds in the Solar Research Site, Universiti Teknologi PETRONAS. The results were analysed and compared with existing studies on solar air heater to show an efficiency of 0.69 and highest temperature of 425K. However, an experimental studies are required to validate the result of the mathematical modelling.